The Science of Sleep - Shook, Sheryl (Open textbook library., 2024)
The Science of Sleep teaches us the vital importance of sleep and how it determines our mental and physical health. It explores the neuroscience of sleep and cultural, social, and political aspects of how people view sleep and are affected by sleep.